Development of IOT Based Secured Emission Test (International Journal of Engineering and Computer Science, 2017)
The IoT based emission test system produces authentic digital emission test certificates. The objective is to overcome some of the disadvantages of the current emission test system where the sensor values are easily altered in the certificates in order to avoid vehicle servicing overhead in case of exceeding the standard emission threshold. Current system of emission test certificate generation requires manually collecting the sensor readings and generating paper-based certificates where veracity of the information on the certificate is not ensured. The proposed technology automatically collects the sensor readings, encrypts the sensor data along with vehicle details and transferring data to the certification authority (CA) for processing over the cloud. The CA is responsible for verifying the authenticity of received data, producing corresponding results and making it available to the authenticated users. This technology induces efficiency, authenticity and integrity by minimizing the manual work.